Identification of Metal Content in Water Samples from Natural Hot Water Sources in Ulumbu Desa Wewo Kecamatan Satar Mese Center Manggarai Regency - Idah, Helena; Suryatika, Ida Bagus Made; Paramarta, Ida Bagus Alit; Gunawan, A.A. Ngurah; Wendri, Nyoman; Rupiasih, Ni Nyoman (BULETIN FISIKA, 2024)
Tests have been conducted on the metal content of Calcium (Ca), Magnesium (Mg), Iron (Fe), Zinc (Zn), Copper (Cu), and Timbal (Pb), on samples of natural hot water Ulumbu Wewo Village Satar Mese Central Manggarai Regency. The research was conducted at the Joint Laboratory of the Faculty of MIPA Udayana University using Atomic Absorption Spectrometry (AAS). The data of the study showed samples of hot water from hot water bathing attractions in Ulumbu Village Wewo Satar Mese District of Central Manggarai Regency contain Ca, Mg, Fe, Zn, Cu, Pb which at each point was different. Calcium content at point 1: 1.6001 mg/L, point 2: 26.9995 mg/L. point 3: 22.3959 mg/L, point 4: 1.1805 mg/L, and point 5: 6.7990 mg/L; magnesium content at point 1: 9.8199 mg/L, point 2: 5.5111 mg/L, point 3: 3.2000 mg/L, point 4: 5.6998 mg/L, and point 5: 8.5598 mg/L; iron content at point 1: 71.8500 mg/L, point 2: 28.7231 mg/L, point 3: 14.3057 mg/L, point 4: 59.3206 mg/L, and point 5: 64.1108 mg/L; the zinc content was only found at point 1 of: 0.5423 mg/L; copper content at point 1: 1.9899 mg/L, point 2: 0.4967 mg/L, point 3: 0.5701 mg/L, point 4: 0.8975 mg/L, and point 5: 1.4201 mg/L and lead content at point 1: 2.7687 mg/L, point 2: 3.8499 mg/L, point 3: 4.4291 mg/L, point 4: 4.8486 mg/L, and point 5: 5.7186 mg/L.